Turist Rehberlerinin Mesleki Motivasyonlarında Tur Üyelerinin Yanlış Davranışlarının Etkisi - Ceylan, Uğur (Muş Alparslan Üniversitesi, 2021)
Tourist guides are influenced by many environmental, social and economic effects during the tour. In addition to these factors, the misbehaviors of the tour group affect the tourist guides. The purpose of this study is to examine the effect of the misbehavior of tour members on the professional motivation of tourist guides during a package tour. The research data is provided from 441 tourist guides working in Istanbul, Nevşehir and Antalya provinces. According to the results of the research, misbehaviors of the tour members towards the environment, laws and personal life affect the professional motivations of the tourist guides. It is determined that the misbehavior of the tour members towards the group does not have an impact on the professional motivation of the tourist guides.

Turist rehberleri tur sırasında birçok çevresel, sosyal ve ekonomik durumdan etkilenmektedirler. Bu unsurlara ek olarak tur grubunun da yanlış davranışları turist rehberlerini etkilemektedir. Bu araştırmanın amacı bir paket tur sırasında tur üyelerinin yanlış davranışlarının, turist rehberlerinin mesleki motivasyonları üzerindeki etkisini incelemektir. Araştırma verileri İstanbul, Nevşehir ve Antalya illerinde çalışan 441 turist rehberinden sağlanmıştır. Araştırma sonuçlarına göre; tur üyelerinin çevreye, yasalara ve kişisel hayata yönelik yanlış davranışları, turist rehberlerinin mesleki motivasyonlarını etkilemektedir. Tur üyelerinin gruba yönelik yanlış davranışları ise, turist rehberlerinin mesleki motivasyonları üzerinde bir etkiye sahip olmadığı tespit edilmiştir.
The Effect of Misbehaviors of Tour Members in the Professional Motivation of Tourist Guides
anemon
Keywords: Tourism; Tourist Guide; Tourist Behavior; Package Tour; Professional Motivation; Turizm; Turist Rehberi; Turist Davranışı; Paket Tur; Mesleki Motivasyon